Analysis of the Influence of Work Environment and Job Satisfaction on Employee Turnover with Employee Relations as a Mediating Variable (A Case Study at PT Zahir International) - Rifa’i, Ade; Suharto, Suharto; Rahmawantari, Dhistianti Mei (Jurnal Multidisiplin Sahombu, 2025)
This study explores the influence of work environment and job satisfaction on employee turnover, with employee relations as a mediating variable. The research was conducted at PT Zahir International using a survey method with all employees as respondents. The analysis employed a structural equation modeling approach with Partial Least Squares to examine both direct and indirect relationships among variables. The findings indicate that work environment and job satisfaction significantly enhance employee relations, while stronger employee relations contribute to reducing turnover intentions. Moreover, employee relations mediate the impact of work environment and job satisfaction on employee turnover, highlighting its strategic role in maintaining organizational stability. The study contributes to the development of human resource management theory by emphasizing the importance of relational dynamics in retaining employees. Practically, the results suggest that organizations should invest in supportive environments and satisfaction policies to strengthen employee relations and reduce turnover.